Manajemen Kualitas Pendidikan Ramah Anak di Lembaga PAUD: Tinjauan dari Persektif Guru dan Orang Tua - Khairunnisa Ulfadhilah; Salsabila Dwi Nurkhafifah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This research aims to explore the quality management of child-friendly education in PAUD through reviewing the perspectives of teachers and parents. In the context of child development, child-friendly education includes a safe, stimulative and inclusive environment, which supports physical, emotional, social and cognitive growth. Qualitative research methods were applied with in-depth interviews with RA Nurul Falah Cirebon teachers and parents. The results show that teachers play an important role in creating a fun and supportive learning atmosphere, using an approach that focuses on children's needs and interests. Meanwhile, parents contribute to optimizing the quality of education through effective communication with institutions and active participation in school activities. These findings emphasize the importance of collaboration between teachers and parents in child-friendly education management to achieve better educational goals. This research recommends that PAUD institutions develop training programs for teachers and increase parental involvement, in order to create a better learning environment that is more responsive to children's needs.